2008
DOI: 10.1088/0022-3727/41/23/234014
|View full text |Cite
|
Sign up to set email alerts
|

Radiative emission and energy deposition in transient luminous events

Abstract: The Imager of Sprites and Upper Atmospheric Lightning (ISUAL) experiment on the FORMOSAT-2 satellite has recently reported that an elve is the most dominant type of transient luminous events (TLEs) and deduced the global occurrence rates of sprites, halos and elves to be ∼1, ∼1 and 35 events/min, respectively (Chen et al 2008 J. Geophys. Res. 113 A08306). In this paper, we report the computed radiative emission and energy precipitation of the TLEs in the upper atmosphere. By analysing 1415 ISUAL TLEs, we found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(119 citation statements)
references
References 51 publications
3
116
0
Order By: Relevance
“…The ISUAL payload globally surveys transient luminous events (TLEs) and other luminous emissions in the upper atmosphere with a side-looking view from the 891 km altitude orbit [Chern et al, 2003;Mende et al, 2005]. Using the satellite information recorded with the TLE events, the altitude and location of the events can be determined by assuming that the bright center of the observed accompanying lightning-illuminated cloud has a height of 10 km [Kuo et al, 2008].…”
Section: The Payload and The Formosat-2 Tle Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ISUAL payload globally surveys transient luminous events (TLEs) and other luminous emissions in the upper atmosphere with a side-looking view from the 891 km altitude orbit [Chern et al, 2003;Mende et al, 2005]. Using the satellite information recorded with the TLE events, the altitude and location of the events can be determined by assuming that the bright center of the observed accompanying lightning-illuminated cloud has a height of 10 km [Kuo et al, 2008].…”
Section: The Payload and The Formosat-2 Tle Observationsmentioning
confidence: 99%
“…Figure 1 shows the theoretical rotational-vibrational spectrum of 1PN 2 , which was computed based on the work of Kuo et al [2008]. The assumed rotational temperature, 220 K, is the ambient temperature of the neutral species at 70 km altitude [Brasseur and Solomon, 1986].…”
Section: Sprite Emissions In the 762 Nm Passbandmentioning
confidence: 99%
“…where ( ) I k m is the band emission from N 2 1P or N 2 LBH given in the work by Kuo et al (2008), and ( ) R m is the relative sensor response function is shown in Fig. 1…”
Section: Instruments and Data Reductionmentioning
confidence: 99%
“…The transmittance calculation follows Lambert's law and the parameters are the same as that used in a work by Kuo et al (2008 and the references therein). The quenching factor q k (h) is defined by the same formula and parameters used in a work by Kuo et al (2008, and the references therein). The band contribution B k for the chosen events that occurred at 90 km is shown in Fig.…”
Section: Instruments and Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation